ROBUST SATELLITE TECHNIQUES FOR VOLCANIC AND SEISMIC HAZARDS MONITORING - Di Bello G.; Filizzola C.; Lacava T.; Tramutoli V.; Marchese F.; Pergola N.; Pietrapertosa C.; Piscitelli S.; Scaffidi I. (My University, 2004)
Several satellite techniques have been proposed to monitor events related to seismic and volcanic activity. A selfadaptive approach (RAT, Robust AVHRR Techniques) has recently been proposed which seems able to recognise space-time anomalies, differently related to such events, also in the presence of highly variable contributions from atmospheric (transmittance), surface (emissivity and morphology) and observational (time/season, but also solar and satellite zenithal angles) conditions. On the basis of NOAA-AVHRR data, the RAT aprroach has already been applied to Mount Etna volcanic ash cloud monitoring in daytime, and to seismic area monitoring in Southern Italy. This paper presents the theoretical basis for the extension of RAT approach also to nighttime volcanic ash cloud detection, together with its possible implementation to lava flow monitoring. One example of successful forecasting (few days before) of a new lava vent opening during the Mount Etna eruption of July 2001 will be discussed in some detail. Progress on the use of the same approach on seismically active area monitoring will be discussed by comparison with previous results achieved on the Irpinia-Basilicata earthquake (MS = 6.9), which occurred on November 23rd 1980 in Southern Italy.